2018
DOI: 10.1155/2018/5047319
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Behaviors of Various Dental Implant Materials under Fatigue

Abstract: e selection of materials has a considerable role on long-term stability of implants. e materials having high resistance to fatigue are required for dental implant applications since these implants are subjected to cyclic loads during chewing. is study evaluates the performance of different types of materials (AISI 316L stainless steel, alumina and its porous state, CoCr alloys, yttriumstabilized zirconia (YSZ), zirconia-toughened alumina (ZTA), and cp Ti with the nanotubular TiO 2 surface) by finite element an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…With the developments in materials science, zirconia implants have been employed to overcome problems with metal allergies and the gray color of titanium implants [ 3 , 4 , 5 ], providing patients with a new choice for dental implant materials [ 6 , 7 ]. In the process of implant repair, mechanical properties [ 8 ] and osseointegration [ 9 ] are key factors that ensure the success and long-term stability of the implant. Studies show that when zirconia implants are tested for static and cyclic fatigue under laboratory conditions, they can withstand the shear force required for implantation and show better mechanical properties than titanium implants [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the developments in materials science, zirconia implants have been employed to overcome problems with metal allergies and the gray color of titanium implants [ 3 , 4 , 5 ], providing patients with a new choice for dental implant materials [ 6 , 7 ]. In the process of implant repair, mechanical properties [ 8 ] and osseointegration [ 9 ] are key factors that ensure the success and long-term stability of the implant. Studies show that when zirconia implants are tested for static and cyclic fatigue under laboratory conditions, they can withstand the shear force required for implantation and show better mechanical properties than titanium implants [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term behavior of implants represents one of the most important concerns, where fatigue fracture is one of the main causes of failure. Indeed, it was recently observed that the bone-implant difference of elastic modulus not only affects the bone to implant penetration but the long term behavior of the implant itself as well: the closer the elastic moduli are, the smoother is the bone- to implant stress transmission, thus improving the long-term mechanical behavior of the implant itself [22]. Titanium alloys, such as α-β alloys show an improved fatigue behavior, compared to pure CpTi, but the dissolution of alloys elements may be toxic for the growing bone [23].…”
Section: Introductionmentioning
confidence: 99%